Influence of clinical and laboratory variables on faecal antigen ELISA results in dogs with canine parvovirus infection. Issue 3 (June 2015) - Proksch, A.L.; Unterer, S.; Speck, S.; Truyen, U.; Hartmann, K.
Highlights False negative faecal antigen ELISA results are frequent for canine parvovirus (CPV). The main reason for a false negative faecal antigen ELISA is a low virus load. Clinical signs are similar in ELISA-positive and -negative dogs. Clinical outcome is similar in ELISA-positive and -negative dogs.